2005
DOI: 10.1175/jpo-2666.1
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic Fluxes in the South Atlantic

Abstract: A box inverse of the World Ocean Circulation Experiment A10 (30°S) and A11 (nominally 45°S) sections in the South Atlantic Ocean was undertaken. The authors find a heat flux across A10 of 0.22 Ϯ 0.08 PW, consistent with previous studies, and a heat flux of 0.43 Ϯ 0.08 PW across A11. The A11 heat flux is lower than some previous analyses of this section but implies a plausible oceanic heat convergence (heat loss to the atmosphere) of 0.21 Ϯ 0.10 PW. The difference is principally due to adding a cyclonic compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 28 publications
8
40
1
1
Order By: Relevance
“…In addition in this study, the box inverse allows for a correction to initial estimates of the mixing between neutral density layers, air sea fluxes and an Ekman transport. All diapycnal fluxes associated with interior mixing or air-sea induced transformation are initialised to zero (McDonagh and King, 2005). As the solution that is estimated is dependent upon the initial field, it is important that the initial field is as representative as possible.…”
Section: Initial Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition in this study, the box inverse allows for a correction to initial estimates of the mixing between neutral density layers, air sea fluxes and an Ekman transport. All diapycnal fluxes associated with interior mixing or air-sea induced transformation are initialised to zero (McDonagh and King, 2005). As the solution that is estimated is dependent upon the initial field, it is important that the initial field is as representative as possible.…”
Section: Initial Fieldmentioning
confidence: 99%
“…Northward BW flow is constrained following Hogg et al (1999), Zenk et al (1999) and McDonagh et al (2002), as 6.9 Sv below the 2 °C isotherm. Within the northern Cape Basin, east of Walvis Ridge (6°E), a zero mass transport constraint is applied below the 2 °C isotherm McDonagh and King, 2005). For the sectionwide upper 80 dbar, a southward, wind-driven estimate for the Ekman transport of 3.3 Sv is included following Bryden et al (2011).…”
Section: Constraints To Circulation and Property Transports On Sectionsmentioning
confidence: 99%
“…Recent studies include those from inverse-box-model studies (McDonagh and King 2005;Ganachaud 2003b;Lumpkin and Speer 2003) and a manual adjustment of geostrophic (plus Ekman) velocities for mass conservation (Talley 2003). Estimates of North Atlantic MOC from these studies are shown on Fig.…”
Section: The Structure Of the Moc Cellsmentioning
confidence: 99%
“…For example the partition between overturning and horizontal heat flux in the subtropical Atlantic at 30°S [24] . At latitudes where the net meridional heat flux is partitioned between the AMOC and horizontal components then it is necessary to supplement the AMOC measurements to ensure that correlated fluctuations of velocity and temperature across the full width of the basin are resolved so that the net meridional heat flux can be determined.…”
Section: Figure 2 Meridional Overturning Stream Function (Sv)mentioning
confidence: 99%